The Driving Factors of Digital Banking Intention and the Role of Customer Experience in Indonesia Banking Industry - Wulandari, Nuri; De Jager, Johan W.; Mahry, Syarifah Endolusia (Universitas Diponegoro, 2024)
As one of the most important industries of a country’s economy, banking is now faced the challenge of competition and demand from the customers to provide excellent service. In addition, the advancement of technology has opened up opportunities to increase service quality of banking offerings. One of the newest approaches is digital banking. Unfortunately, the literature is still limited in this area especially on the customer adoption of this service. The objective of this study is to find driving factors that contributes to the intention to use and reuse digital banking especially in generation Z and Millenials. It is hypothesized that there are six factors that might drive the intention, includes performance expectancy, effort expectancy, social influence, perceived service quality and hedonic motivation. It has also argued that intention is mediated by customer experience. Quantitative research was conducted to 105 respondents in Indonesia where digital banking is flourishing. The results provide valuable insights to the factors of digital banking usage intention in the future.